Analysis of the interinstitutional relationship of collaboration between the Ministry of Interior and National Police of Colombia, from an administrative perspective - Ayala Cubillos, Evelyn Stella (Universidad Pedagógica y Tecnológica de Colombia, 2014)
In Colombia the Public Administration can generate interinstitutional relationship, for the collaboration between different institutions and so from exercise of their functions may join together through agreements that facilitate the implementation of public policy. The purpose of this article is the specific analysis of aspects of organizational management that affect the financial performance, but from the point of view of an interinstitutional collaborative relationship.  An analysis was done for a case study of the relationship between the Ministry of Interior and the National Police of Colombia, as part of the Policy and the National Security Strategy and Civic Coexistence.  The analysis allowed demonstrates the need to strengthen the planning process in coordination between the parties involved in the collaborative relationship and so they can better articulate their resources. This will make it possible to add value to the experience of the institutions involved, their processes and procedures, and thus enhancing the agreements reached.